A character sketch and a text in discovering the past of Circassia: J.S. Bell - Angela Kaplanovna Cheucheva; Lyudmila Rashidovna Khut (Вестник Майкопского государственного технологического университета, 2023)
The article analyzes the literary activities of J.S. Bell, the British emissary in Circassia in 1830s. Particular attention is paid to the historical aspects of his activity in establishing communication between the Adyghs (the Circassians) of the North-West Caucasus and propagating the ideas of the Circassian liberation movement in the UK. The conclusion is substantiated that J. S. Bell’s activity, firstly, reflected two interconnected levels of the British diplomacy - an entrepreneurial level and a political one; secondly, it contributed to the formation of a positive image of Circassia in the European consciousness. It is emphasized that J.S. Bell’s literary heritage and his position on the Circassian issue give an idea ofthe views of a part of British society interested in activating English politics on the east coast of the Black Sea. It is concluded that J.S. Bell’s book goes beyond the scope of the memoir literature of an ordinary traveler. There is a lot of information about the organization of the daily life of the Adygh society, and a detailed analysis of the realities of political activities of the Adyghs is given. J.S. Bell’s literary heritage is a unique factual and illustrative material about the inner life of Circassia. The authors concluded that the establishment of relations between the British and the Adygh peoples contributed to political interaction and actualization of the Circassian issue in the international arena. Issues of political and cultural communication, formation of a positive image of the country are the topics that deserve close analysis.